Face Recognition Technology: Benefits, Applications, and Challenges (International Journal of Scientific Research and Management (IJSRM), 2025)
Facial recognition technology has emerged as a vital innovation in the field of biometric identity verification, offering benefits such as enhanced security and user convenience. This paper explores its various applications, including public safety, access control, and consumer devices. Despite the advantages, significant challenges such as algorithmic bias, lighting variations, and privacy concerns remain, requiring further research and technological advancements.